Combination Delivery of Alpha-Tocopheryl Succinate and Curcumin Using a GSH-Sensitive Micelle (PAH-SS-PLGA) to Treat Pancreatic Cancer - Tilahun Ayane Debele; Hung-Chang Wu; Shang-Rung Wu; Yan-Shen Shan; Wen-Pin Su (MDPI AG, 2020)
Pancreatic cancer is one of the highest causes of mortality throughout the world; thus, it requires an effective treatment strategy. Some chemotherapeutic agents used in the clinics or under clinical trials are hydrophobic and have poor aqueous solubility; consequently, they also have minimal systemic bioavailability. Nanoparticle-based drug delivery tactics have the potential for overcoming these limitations and enhancing their therapeutic efficacy. Herein, a glutathione (GSH)-sensitive micelle (PAH-SS-PLGA) was synthesized for the combined delivery of alpha-tocopheryl succinate (TOS) and curcumin to improve its therapeutic efficacy. The chemical structures of PAH-SS-PLGA were analyzed using Proton Nuclear Magnetic Resonance (1H-NMR) and Fourier Transform Infrared (FTIR) spectroscopy, whereas the particle size, zeta potential, and surface morphology were observed using dynamic light scattering (DLS) and transmission electron microscopy (TEM). In vitro drug release results revealed that more TOS and curcumin were released in the presence of GSH (5 mM) than the physiological pH value. Fluorescence microscopy images revealed that nanoformulated curcumin/rhodamine was uptaken by PAN02 pancreatic cancer cells. In vitro cytotoxicity assays showed higher cytotoxicity for nanoformulated TOS and/or curcumin than free TOS and/or curcumin. In addition, higher cytotoxicity was observed for combination drugs than free drugs alone. Most interestingly, at all tested concentrations of nanoformulated drugs (PAH-SS-PLGA, TOS, and curcumin), the calculated combination index (CI) value was less than one, which shows that TOS and curcumin have a synergistic effect on cellular proliferation inhibition. Overall, synthesized co-polymers are the best carriers for combination drugs, TOS, and curcumin, because they enhance the therapeutic efficacy and improve pancreatic cancer treatments.